Constructing Religious Identity in Social Media: A Sociolinguistic Study of Spoken Discourse among Islamic Preachers and Influencers - Cyrilla, Nadhia I’zaz; Sanukerti, Yunda Refia Atma (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research studies the background of the formation of religious identity, especially through spoken language on social media by Islamic preachers and influencers. Through the uploaded video content, currently, social media is the main place for someone to express themselves, including showing their religious identity. This research uses a qualitative approach in sociolinguistic studies, by using language style theory from Martin Joos and identity concepts from Mary Bucholtz and Kira Hall. Data in the form of speech transcribed from several videos of Islamic preachers and influencers on social media. This research focuses on language style, level of formality, and communication methods used in forming religious identity. Research results show that Islamic preachers tend to use more formal and assertive language, while influencers use language that is more relaxed and closer to the audience. This shows that differences in language styles affect the way someone displays their religious identity on social media.